An in-Vivo Daily Self-Report Approach to the Assessment of Outcomes of Two Psychotherapies for Women With Posttraumatic Stress Disorder. Issue 1 (January 2022) - Ford, Julian D.; Tennen, Howard; Grasso, Damion J.; Chan, Grace
Highlights: Affect regulation and interpersonal therapies have proven effective in treating PTSD. This is the first study to use a daily self-report measure to evaluate PTSD psychotherapies. Affect regulation therapy improved women's daily symptoms, self-regulation, and affect. Interpersonal therapy reduced women's daily PTSD symptoms and dysregulation. Daily self-report data can extend therapy research findings to include daily life outcomes. Abstract: Emotion regulation and interpersonal psychotherapies that do not require trauma memory processing have been shown to be effective in treating posttraumatic stress disorder (PTSD). This study used a novel method to assess in vivo outcomes in a randomized clinical trial with women ( N = 147; ages 18–54; 61% of color; 94% low income) with full (79%) or partial (21%) PTSD. Participants were assigned to affect regulation or interpersonal therapy, or wait-list, and completed daily self-reports for 2 to 4 weeks at baseline and up to 30 days at posttest. Mixed model regression analyses tested pre-post change on five factor analytically derived aggregated daily self-report scores. Emotion regulation-focused therapy was associated with reduced PTSD symptoms, dysregulation, and negative affect, and improvement in adaptive self-regulation and positive affect. Interpersonal-focused therapy was associated with reduced PTSD symptoms and dysregulation. Although both therapies were associated with reduced PTSD symptoms, whether this was due to nonspecific factors rather than the treatments per se could not be determined. Daily self-report data warrant further investigation in psychotherapy research with disorders such as PTSD, in order to assess affective and interpersonal dysregulation and adaptive regulation as they occur in daily life.